Christianity : the first three thousand years - MacCulloch, Diarmaid; MacCulloch, Diarmaid (New York : Penguin, 2011)
Offers a history of Christianity ranging back to the origins of the Hebrew Bible and covering the world, following the three main strands of the Christian faith, to teach modern readers how Jesus' message spread and how the New Testament was formed. MacCulloch follows the Christian story to all corners of the globe, filling in often neglected accounts of conversions and confrontations in Africa and Asia. He explores the roots of the faith that galvanized America, charting the rise of the evangelical movement from its origins in Germany and England. MacCulloch introduces the monks and crusaders, heretics and saints, slave traders and abolitionists, and he discovers Christianity's essential role in driving the Enlightenment and the Age of Exploration, and shaping the course of World Wars I and II. --Adapted from publisher description of 2010 edition
A millennium of beginnings (1000 BCE-100 CE). -- Greece and Rome (c. 1000 BCE-100 CE) -- Israel (c. 1000 BCE-100 CE) -- One Church, one faith, one Lord? (4 BCE-451 CE). -- A crucified messiah (4 BCE-100 CE) -- Boundaries defined (50 CE-300) -- The Prince: ally or enemy? (100-300) -- The Imperial Church (300-451) -- Vanishing futures: East and South (451-1500). -- Defying Chalcedon: Asia and Africa (451-622) -- Islam: the great realignment (622-1500) -- The unpredictable rise of Rome (300-1300). -- The making of Latin Christianity (300-500) -- Latin Christendom: new frontiers (500-1000) -- The West: universal emperor or universal pope? (900-1200) -- A Church for all people? (1100-1300) -- Orthodoxy: the Imperial faith (451-1800). -- Faith in a new Rome (451-900) -- Orthodoxy: more than an empire (900-1700) -- Russia: the third Rome (900-1800) -- Western Christianity dismembered (1300-1800). -- Perspectives on the true Church (1300-1517) -- A house divided (1517-1660) -- Rome's renewal (1500-1700) -- A worldwide faith (1500-1800) -- Protestant awakenings (1600-1800) -- God in the dock (1492-present). -- Enlightenment: ally or enemy? (1492-1815) -- Europe re-enchanted or disenchanted? (1815-1914) -- To make the world Protestant (1700-1914) -- Not peace but a sword (1914-60) -- Culture wars (1960-present)
Originally published in the United States of America by Viking Penguin, 2010
Published in Great Britain as: A history of Christianity by Allen Lane, an imprint of Penguin Books, Ltd
Includes bibliographical references and index
Keywords: Church history; Christianity; Judaism -- History; Rome -- Religion -- History; History